Properties and N-terminal amino acid sequences of three Erythrina lectins from Costa Rica (Leguminosae) - Aragón-Ortiz, Federico (Universidad de Costa Rica, 1994)
Three Erythrina lectins, from E. fusca, E. globocaliz and E. costaricensis were isolated by affinity chromatography. The lectins are glycoproteins with a monomenc molecular weight of 28 000. They agglutinate human erythrocytes irrespective of blood type and the activity was inhibited by N-acetyl-galactosamine, galactose and lactose. The N-terminal amino acid sequences of the three lectins were deterrnined by automated Edman degradation of the native proteins. Comparison with the sequences of ten other legume lectins revealed extensive homology. The N-terminal amino acid for E.fusca is Val, and Ala for E. globocaliz and E. costaricensis.